The role of CRTC genes in the development of the zebrafish embryo - Fang, Trixy Xinyi (2012)
CRTC1 (CREB-regulated transcription coactivator 1) is involved in regulation of CREB-target gene expression and transcription activation by MEIS1 (myeloid ecotropic viral integration site 1) protein. Biological functions of CRTC1 have been associated with cancer metastasis, neuronal morphogenesis in mouse and longevity in C.elegans. However, the role of CRTC1 in zebrafish embryonic development has not been characterized yet. Previous unpublished observations showed that morpholino-mediated knockdown of CRTC1 results in a ‘curly tail down’ phenotype of zebrafish morphants. Based on these observations, whole mount in situ hybridization was performed to study muscle-specific and notochord gene expression in crtc1 morphants. Notochords of morphants showed persistent shh